Perancangan Sistem Pengajuan Pemasangan Baru Layanan Wifi.Id Di PT. Telkom Regional-1 Sumatera - Noor, Fredy; Khairani, Nurul (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
The rapid development of information technology encourages telecommunication companies to continue to innovate, including PT. Telkom Regional-1 Sumatra which provides Wifi.id services. This study aims to design a new installation submission system for web-based Wifi.id services to improve the efficiency and speed of the installation process. The system is designed using PHP and CSS programming languages, as well as MySQL as the database. The design method involves the use of flowcharts, sitemaps, context diagrams, entity relationship diagrams (ERDs), and data flow diagrams (DFDs) to ensure the system is well structured. The results of the study show that the designed system can make it easier for the people of North Sumatra to apply for the installation of Wifi.id services efficiently and transparently. This system also increases the speed and effectiveness of the installation process, thus providing benefits for both customers and PT. Telkom Regional-1 Sumatra. With the implementation of this system, the installation application process becomes more organized, supports the improvement of service quality, and has a positive impact on the customer experience